Oitavo dia: a gamearte nos jogos de tabuleiro - Custódio, José Antonio Loures (2016)
Board games are cultural reflexes, born as religious and mythological rites, took up the entertainment object condition, and finally, were subverted and transformed into an art form. This theoretical and practical character dissertation investigates this last stage, and research artists and works of analog gamearte aiming to understand the creative process behind the art of board games, still little explored field. This research presents a pioneer, because there are no studies on the game boards through art in Brazil. The first categorization of Brazilian board games that belong to the gamearte settings. It is also proposed to present the relevance and persistence of analog game in a digital contemporaneity. These investigations serve as a reflective theoretical framework for the simultaneous development of poetic practice this research, an authorial artistic board game.